Making your case (London : Video Arts, 1991)
We see a young manager preparing for her first major presentation to the Board. Every mistake and common errors preparation, structure and delivery made were highlighted, and a successful error-free presentation were shown instead
Bibliographical information is taken from the publisher's catalogue
Keywords: Public speaking